Microbiological and histopathological study in fishes neon tetra (paracheirodon innesi) from the Peruvian amazon - Palacios H., Shirley (2015)
The aim of this study was to determine the presence of infectious agents by microbiological and histopathological studies in the neon tetra (Paracheirodon innesi), an Amazonian ornamental fish. A total of 168 fish were randomly collected from the aquarium of an ornamental fish retail collector in Iquitos, Peru. For the microbiological study, kidney and spleen samples were collected during the necropsy of 84 specimens, and bacteria were isolated in trypticase soy agar (TSA), Citophaga (AO) and Middlebrook 7H9, while identification was done through Gram staining and biochemical analysis. The histopathological study was conducted in the remaining 84 fish. Bacteria isolated were of genera Flavobacterium, Staphylococcus, Carnobacterium, Pseudomonas, Enterococcus, Bacillus and of the Enterobacteriaceae family. In gills was observed laminar hyperplasia, fusion of lamellae and Mixosporidia spores at the tips of the lamellae; in the intestine was observed epithelial hyperplasia of the bowel and spores of Microsporidium in the intestinal villi; in the liver was found hydropic and fatty degeneration and a parasitic granuloma; in kidneys was found peritubular edema and hydropic degeneration; and in the muscular skeletal was found necrosis, presence of Mixosporidium cysts, granulomas, and spores of Microsporidium, Pleistophora and Heterosporis.